1998
DOI: 10.1017/s0952523898154160
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fixational eye movements on the response of neurons in area MT of the macaque

Abstract: We analyzed the relationship between eye movements and neuronal responses recorded from area MT in alert monkeys trained to maintain visual fixation during the presentation of moving patterns. The monkeys made small saccades which moved the eyes with velocities that spanned the sensitivity range of MT neurons. The saccades evoked changes in the neuronal response that depended upon (1) the level of stimulus-evoked activity amidst which the saccade occurred and (2) the direction of the saccade relative to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 38 publications
18
127
3
Order By: Relevance
“…Microsaccades occurred with an average rate of more than two times per second, consistent with previous reports (Bair and O'Keefe, 1998;Martinez-Conde et al, 2000Engbert and Mergenthaler, 2006). A recent study demonstrated that MSs in human subjects occur with a distinct temporal structure (OteroMillan et al, 2008).…”
Section: Identification and Temporal Distribution Of Microsaccadessupporting
confidence: 77%
See 1 more Smart Citation
“…Microsaccades occurred with an average rate of more than two times per second, consistent with previous reports (Bair and O'Keefe, 1998;Martinez-Conde et al, 2000Engbert and Mergenthaler, 2006). A recent study demonstrated that MSs in human subjects occur with a distinct temporal structure (OteroMillan et al, 2008).…”
Section: Identification and Temporal Distribution Of Microsaccadessupporting
confidence: 77%
“…We confirmed a linear relation between both parameters (Fig. 1 B) (r ϭ 0.812, p Ͻ 0.01, t ϭ 382) (Zuber and Stark, 1965;Bair and O'Keefe, 1998;Martinez-Conde et al, 2000, 2006Hafed et al, 2009).…”
Section: Identification and Temporal Distribution Of Microsaccadessupporting
confidence: 69%
“…This is larger than in most studies, although there is also considerable variability between the average microsaccade amplitudes described in past reports, which include 0.8° (Bair and O'Keefe, 1998) (Ko et al, 2010;Poletti and Rucci, 2010), and 0.23° ( Hafed et al, 2009).…”
Section: Discussioncontrasting
confidence: 39%
“…On the one hand, microsaccades modulate spiking activity in the visual cortex (Bair and O'Keefe 1998;Leopold and Logothetis 1998;Martinez-Conde et al 2000, 2002Snodderly et al 2001;Martinez-Conde et al 2004, for an overview).…”
Section: Introductionmentioning
confidence: 99%